Etnobotani Tumbuhan Obat di Desa Siharangkarang - Ginting, Nurmaini (BIOLINK (Jurnal Biologi Lingkungan, Industri, Kesehatan), 2016)
This research was conducted in the village of Siharangkarang, Hutaimbaru, Padangsidimpuan, North Sumatra. Data obtained from the open interviews. Informant selection technique used for the pre- observation is purposive sampling method. The next interview was conducted by sampling snowbowling. It Found 41 species of medicinal plants are commonly used by people in the village Siharangkarang. 30 species of medicinal plants of 41 species that have been known to have been cultivated by the people, be it at home or  in the garden. The using of plants as medicine by the people in the village Siharangkarang cover all part  of the plant, but  the most widely of that part who  used are the leaves.